2016
DOI: 10.5144/0256-4947.2016.386
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of IgG-mediated food intolerance among patients with allergic symptoms

Abstract: BACKGROUNDFood intolerance mediated by food specific IgG antibodies has been implicated in a variety of disorders.OBJECTIVESTo assess the prevalence of food specific IgG antibodies among patients clinically presenting with allergic symptoms lacking laboratory evidence of allergy.DESIGNDescriptive retrospective cross-sectional study.SETTINGKing Khalid University Hospital, Riyadh between 2010–2015.PATIENTS AND METHODSPatients were screened for food specific IgG antibodies. All symptomatic patients lacking labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 18 publications
(30 reference statements)
5
35
0
6
Order By: Relevance
“…Some investigations have reported that the elderly population may be more likely to develop food allergies than younger individuals[47]. However, other studies have revealed that the younger age group had higher levels of food-specific IgG compared with older people[45,48], which is similar to the results in the present study. Maturation of intestinal mucosa with increasing age may influence food intolerance resulting in differential immune responses at different ages.…”
Section: Discussionsupporting
confidence: 90%
“…Some investigations have reported that the elderly population may be more likely to develop food allergies than younger individuals[47]. However, other studies have revealed that the younger age group had higher levels of food-specific IgG compared with older people[45,48], which is similar to the results in the present study. Maturation of intestinal mucosa with increasing age may influence food intolerance resulting in differential immune responses at different ages.…”
Section: Discussionsupporting
confidence: 90%
“…Food intolerance is an allergic disease mediated by immunoglobulin G (IgG). When the body ingests intolerant food, the specific IgG antibody produced by the immune system combines with the allergen in food to form immunity complex, causing varying reactions of the body, involving the digestive system, respiratory system and skin (1). Food intolerance is becoming more and more common with an incidence rate of 20% to 45%, which has become one of the hottest issues in research at home and abroad (2).…”
Section: Introductionmentioning
confidence: 99%
“…We assessed only 20 types of food hypersensitivity using the IgE test and did not evaluate antigens other than those 20 and antigen-specific IgG, which implies a biomarker for delayed allergy and food intolerance. 39 However IgE-mediated food hypersensitivity is caused mainly by particular antigens evaluated in our research, 30 and basically, food allergies are caused through immediate-allergy, which is evaluated using the IgE test. The target of antiallergy drugs, such as an H1 blocker, and IgE antibody is IgE-mediated reaction.…”
Section: Discussionmentioning
confidence: 92%